Perceptions of Brain-Machine Interface Technology among Mothers of Disabled Children - Lucy Diep; Gregor Wolbring (Disability Studies Quarterly, 2015)
Communication technologies are constantly transforming the way we communicate and interact with each other, and with our environment, with its impact affecting everyone including disabled people and the groups linked to them. The brain-machine interface (BMI) is one example of an emerging communication technology envisioned to transform the way we communicate and interact with each other and our environment in the near future. One group targeted to use BMI technology and impacted by others using BMI are disabled people. For disabled people and their families, the impact and implications of adopting BMI technologies is important to understand so they can make informed decisions and advocate for policies governing the technology's application to decrease negative and increase positive outcomes. In this study, we interviewed nine mothers of disabled children, with no prior knowledge of BMI technology, to explore their perceptions and attitude toward the technology. Five main themes emerged from our findings: the potential benefit to aid mothers to interpret their children's needs; the potential benefit to expand a child's social network; the preference for non-invasive BMI approach; impact of BMI use by non-disabled people and cost and qualification barriers.
Keywords: brain-machine interface; communication; mothers; disabled children; ethics; advocacy; anticipatory governance